Large size (>100‐μm) microplastics are not biomagnifying in coastal marine food webs of British Columbia, Canada. Issue 7 (4th July 2022) - Covernton, Garth A.; Cox, Kieran D.; Fleming, Wendy L.; Buirs, Brittany M.; Davies, Hailey L.; Juanes, Francis; Dudas, Sarah E.; Dower, John F.
Abstract: Microplastics (MPs) contamination in marine environments is of increasing concern, as plastic particles are globally ubiquitous across ecosystems. A large variety of aquatic taxa ingest MPs, but the extent to which animals accumulate and transfer MPs through food webs is largely unknown. In this study, we quantified MP uptake in bivalves, crabs, echinoderms, and fish feeding at different trophic levels at three sites on southern Vancouver Island. We paired stable‐isotope food web analysis with MP concentrations in digestive tracts across all trophic levels and in fish livers. We then used Bayesian generalized linear mixed models to explore whether bioaccumulation and biomagnification were occurring. Our results showed that MPs (100–5000 μm along their longest dimension) are not biomagnifying in marine coastal food webs, with no correlation between the digestive tract or fish liver MP concentrations and trophic position of the various species. Ecological traits did, however, affect microplastic accumulation in digestive tracts, with suspension feeder and smaller‐bodied planktivorous fish ingesting more MPs by body weight. Trophic transfer occurred between prey and predator for rockfish, but higher concentrations in full stomachs compared with empty ones suggested rapid excretion of ingested MPs. Collectively, our findings suggested the movement of MP through marine food webs is facilitated by species‐specific mechanisms, with contamination susceptibility a function of species biology, not trophic position. Furthermore, the statistical methods we employ, including machine learning for classifying unknown particles and a probabilistic way to account for background contamination, are universally applicable to the study of microplastics. Our findings advance understanding of how MPs enter and move through aquatic food webs, suggesting that lower‐trophic‐level animals are more at risk of ingesting >100‐μm MPs, relative to higher‐trophic‐level animals. Our work also highlights the need to advance the study of <100‐μm MPs, which are still poorly understood and may need to be considered separately in ecological risk assessments.